Research trends linking collaborative learning to student well-being: A systematic review - Thathit Manon Andini; Rosalin Ismayoeng Gusdian; Joko Widodo (Research and Development in Education (RaDEn), 2026)
Background-In recent years, research attention to collaborative learning (CL) and student well-being has increased, reflecting the growing need to understand how both constructs contribute to learning quality and students’ lived experiences in higher education.Objectives-This PRISMA-guided systematic review maps research trends on the CL–well-being relationship indexed in Scopus from January 2015 to November 2025. Method-Using a structured search strategy, screening, and eligibility checks, 107 open-access empirical journal articles met the inclusion criteria. Descriptive analyses were conducted to examine publication growth, geographic and disciplinary distributions, and dominant patterns using keyword networks, co-citation structures, and highly cited documents. Results-Findings indicate sustained growth—particularly around 2020–2021—alongside concentration of contributions in Global North contexts and the emergence of interlinked themes relating CL to belongingness, peer support, stress reduction, and digitally mediated collaboration. Conclusions-The review highlights persistent methodological and contextual gaps, especially limited longitudinal designs and underrepresentation of Global South perspectives. Future research is recommended to deepen thematic synthesis, broaden cultural contexts, and strengthen cross-national collaboration to develop more inclusive and robust knowledge on how CL supports student well-being.